Shaping Urban Futures in Mongolia Shaping Urban Futures in Mongolia - Plueckhahn, Rebekah (Economic Exposures in Asia, 2020)
What can the generative processes of dynamic ownership reveal about how the urban is experienced, understood and made in Ulaanbaatar, Mongolia? Shaping Urban Futures in Mongolia provides an ethnography of actions, strategies and techniques that form part of how residents precede and underwrite the owning of real estate property - including apartments and land - in a rapidly changing city. In doing so, it charts the types of visions of the future and perceptions of the urban form that are emerging within Ulaanbaatar following a period of investment, urban growth and subsequent economic fluctuation in Mongolia's extractive economy since the late 2000s.